Optimization of Intensive Therapy Strategies for Sepsis on the Basis of the Clinicostatistical Model PIRO - L. A. Maltseva; A. O. Volkov (Общая реаниматология)
Objective: to develop a variant of the clinicostatistical model PIRO, by making retrospective and prospective analyses of cases of sepsis, severe sepsis, and septic shock, to carry out its clinical trial, and to estimate its prognostic value and expert capacities. Subjects and methods. Critically ill patients with multiple organ dysfunctions, who had signs of an active systemic inflammatory response by the ACCP/SCCM criteria (1992), the severity of the underlying condition of an APACHE II Score of 10 or more, and manifestations of multiple organ dysfunctions by the SOFA scale, were enrolled for the study. Among them, the men and women were 69 and 57%, respectively; their mean age was 42.0±1.6 years. While developing a variant of the PIRO model, the authors determined the domains of its parameters as values in the presence of these or those signs of premorbidity (Charlson Comorbidity Index, 1987), infection (the classification worked out by R. A. Weinstein in 2001 and modified by the author), a systemic response to infection (the classical signs of SIRD and the diagnostic markers of sepsis, proposed by M. M. Levy et al. (SSC), multiple organ dysfunctions/failures (SOFA scale) in a specific patient. Results. The data given in the present paper suggest that the use of the new diagnostic markers of sepsis in addition to the classical criteria of SIRS allowed its diagnosis to be made in the highly specific fashion; the PIRO model variant designed by the authors has heuristic, predictive, and expert capacities; it made it possible to reliably determine the outcome of the disease at an early stages of sepsis, by using the basic parameters affecting the progression and outcome of the disease and to establish that the patients who had experienced a septic episode had persistent organ dysfunction, more severe premorbid state, and poorer quality of life. Conclusion. The application of the PIRO model makes it possible not only to choose a timely and full intensive therapy strategy, but also to prevent the progression of persistent organ dysfunction/failure after a sustained septic episode. Key words: sepsis, multiple organ dysfunction, PIRO system.